Parathyroid Carcinoma in the Setting of Tertiary Hyperparathyroidism: Case Report and Review of the Literature. (2nd December 2020) - Cappellacci, Federico; Medas, Fabio; Canu, Gian Luigi; Lai, Maria Letizia; Conzo, Giovanni; Erdas, Enrico; Calò, Pietro Giorgio
Abstract : Introduction . Parathyroid carcinoma is one of the rarest cancers in normal population, and it is extremely uncommon in the setting of tertiary hyperparathyroidism. Indeed, only 24 cases have been reported in the literature. Presentation of the Case . We report the case of parathyroid carcinoma in a 51-year-old man, with a history of end-stage renal disease due to a horseshoe kidney treated with haemodialysis since 2013. He came to our attention due to an increase in calcium and parathyroid hormone serum levels. Neck ultrasound (US) showed a solid hypodense mass, probably the right inferior parathyroid gland, with an estimated size of 25 × 15 × 13 mm; the 99mTc-sestamibi SPECT/CT scan revealed a large radiotracer activity area in the right cervical region, compatible with a hyperfunctioning right inferior parathyroid gland. So, a tertiary hyperparathyroidism diagnosis was made. In April 2018, resection of three parathyroid glands was performed. Histopathological examination demonstrated the right inferior parathyroid gland specimen to be a parathyroid carcinoma, due to the presence of multiple, full-thickness, capsular infiltration foci, and a venous vascular invasion focus. Discussion . Diagnosis of parathyroid carcinoma in tertiary hyperparathyroidism is remarkably complex because of the lack of clinical diagnostic criteria and, in many cases, is made postoperatively at histopathological examination. Conclusion . To date, radical surgery represents the mainstay of treatment, with a five- and ten-year survival rates overall acceptable.